Noise contribution analysis of a U-shaped girder bridge with consideration of frequency dependent stiffness of rail fasteners. (30th March 2023) - Song, Xiaodong; Wu, Hao; Jin, Hao; Cai, C.S.
Highlights: The frequency dependence of rail fastener stiffness has obvious influence on vibration and noise radiation of urban rail transit bridges. The piers can affect the vibration distribution of the bridge, resulting in larger dynamic response at support than mid span. Acoustic contribution and distribution of the piers and U-shaped girder is investigated. Abstract: The U-shaped girder has been widely constructed in urban rail transit systems, and related investigations have been conducted to study the vibration and noise radiation. However, the constant stiffness fastener (CSF) model was used in most previous research when simulating the noise radiation of U-shaped girder bridges. Moreover, the sound radiation from piers was generally ignored in noise prediction. In this study, a numerical model of U-shaped girder bridge with piers and frequency dependent stiffness fasteners (FDSF) was developed. Then, the frequency domain method was used to simulate both the dynamic response of the bridge and the associated noise radiation. Field tests were also conducted to verify the accuracy of the proposed method. Finally, the acoustic contribution and sound pressure distribution of the pier and girder were discussed based on the FDSF model. The research shows the simulated dynamic responses agree well with the experimental results in the frequency range of interest (20 to 200 Hz). The predicted noise by using FDSF model is closer to measured results than the case using constant fastener stiffness, which indicates that the frequency dependence of rail fasteners should be considered in noise simulation. The piers have obvious influence on the vibration and noise radiation of the bridge structure, especially at the support pier section, where the noise level is larger than that at the mid span. The structure-borne noise from the pier is distributed in a narrow frequency band (50 to 80 Hz), and only affects the acoustic field in the limited space around the pier. In contrast, the sound contribution of the girder noise to the total noise level is dominant in most of the area.